Immune homeostasis and disorder in the testis – Roles of Sertoli cells. (August 2022) - Chen, Ran; Wang, Fei; Chen, Yongmei; Han, Daishu
Abstract: The mammalian testis requires a highly organized microenvironment for the execution of its main functions, sperm production and testosterone synthesis. The testis possesses an immunoprivileged status essential for the protection of immunogenic male germ cells from detrimental immune responses. To counteract microbial infections, the tissue-specific cells are well equipped with innate defense machineries, termed pattern recognition receptors (PRRs), that can initiate innate immune responses. However, PRR-initiated innate immune responses in testicular cells may disrupt the immunoprivileged status and result in orchitis, thereby impairing spermatogenesis and testosterone synthesis. The mechanisms underlying the innate defense system and immunological pathophysiology in the testis have been intensively studied. Testicular immune homeostasis and disorders are regulated by a coordination of the tissue structure and cellular functions. This article focuses on the pivotal roles that Sertoli cells play in regulating testicular immune homeostasis by facilitating the blood-testis barrier, phagocytosis, paracrine, and innate immune responses. Highlights: SCs maintain testicular immune homeostasis via several mechanisms. SCs modify systemic immunity. SCs initiate testicular innate immune response. SCs establish the blood-testis barrier. SCs phagocytose germ cell antigens.